Luminescent Quadrupolar Borazine Oligomers: Synthesis, Photophysics, and Two‐Photon Absorption Properties. Issue 50 (30th October 2015) - Chen, Pangkuan; Marshall, Ariel S.; Chi, San‐Hui; Yin, Xiaodong; Perry, Joseph W.; Jäkle, Frieder
Abstract: A set of monodisperse bent donor–acceptor–donor‐type conjugated borazine oligomers, B n N n +1 ( n =1–4), incorporating electron‐rich triarylamine donor and electron‐deficient triarylborane acceptor units has been prepared through an iterative synthetic approach that takes advantage of highly selective silicon–boron and tin–boron exchange reactions. The effect of chain elongation on the electrochemical, one‐ and two‐photon properties and excited‐state photodynamics has been investigated. Strong intramolecular charge transfer (ICT) from the arylamine donors to boryl‐centered acceptor sites results in emissions with high quantum yields ( Φ fl >0.5) in the range of 400–500 nm. Solvatochromic effects lead to solvent shifts as large as ∼70 nm for the shortest member ( n =1) and gradually decrease with chain elongation. The oligomers exhibit strong two‐photon absorption (2PA) in the visible spectral region with 2PA cross sections as large as 1410 GM ( n =4), and broadband excited‐state absorption (ESA) attributed to long‐lived singlet–singlet and radical cation/anion absorption. The excited‐state dynamics also show sensitivity to the solvent environment. Electrochemical observations and DFT calculations (B3LYP/6‐31G*) reveal spatially separated HOMO and LUMO levels resulting in highly fluorescent oligomers with strong ICT character. TheB n N n +1 oligomers have been used to demonstrate the detection of cyanide anions with association constants of log K >7. Abstract : Extension of conjugation in oligomersB n N n +1 as confirmed by GPC analysis (see figure) results in bathochromic shifts in the one‐photon absorption (1PA) and large increases in the two‐photon absorption (2PA) cross sections. Solvatochromic emission effects due to intramolecular charge transfer diminish with increasing chain length, causing an unexpected hypsochromic shift with extension of conjugation in polar solvents.